2019
DOI: 10.1002/jbio.201800436
|View full text |Cite
|
Sign up to set email alerts
|

The use of Fourier‐transform infrared spectroscopy to characterize connective tissue components in skeletal muscle of Atlantic cod (Gadus morhua L.)

Abstract: In the present study, Fourier‐transform infrared spectroscopy (FTIR) is investigated as a method to measure connective tissue components that are important for the quality of Atlantic cod filets (Gadus morhua L.). The Atlantic cod used in this study originated from a feeding trial, which found that fish fed a high starch diet contained relative more collagen type I, while fish fed a low starch (LS) diet contained relative more glycosaminoglycans (GAGs) in the connective tissue. FTIR spectra of pure commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…Thus, our developed, porous gel might be suitable for cell migration and growth. The FTIR spectrum showed the typical bands of amide I, II, and III for the cross-linked ADSC ECM gel, and the presence of amide III relating to C-N stretching and NH reveals the triple helical structure of collagen is preserved [ 66 , 67 ]. Moreover, the spectrum of the cross-linked ADSC ECM gel showed a decrease in the characteristic peak of amine (–NH 2 ) stretch at 1541 cm −1 , and this result was consistent with genipin cross-linked tissue-derived ECM [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our developed, porous gel might be suitable for cell migration and growth. The FTIR spectrum showed the typical bands of amide I, II, and III for the cross-linked ADSC ECM gel, and the presence of amide III relating to C-N stretching and NH reveals the triple helical structure of collagen is preserved [ 66 , 67 ]. Moreover, the spectrum of the cross-linked ADSC ECM gel showed a decrease in the characteristic peak of amine (–NH 2 ) stretch at 1541 cm −1 , and this result was consistent with genipin cross-linked tissue-derived ECM [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prominent peak at 1451-6cm -1 and a smaller band at 1336-8cm -1 were attributed to the wagging of proline CH 2 and the presence of side chain vibrations, respectively [44]. The Amide III bands displayed a peak at 1202cm -1 and a shoulder peak around 1244cm -1 .…”
Section: Ir Spectral Profile Of Chmentioning
confidence: 99%
“…The presence of GPO triplets confers endo-exo imino ring pucker motions that, coupled with the peptide backbone, leads to expansion and compression of the regions surrounding the triplets [45]. and side-chain vibrations in collagen respectively [44]. The stretches around 1400-1450 and 983-1058cm -1 corresponded to carbonates and skeletal stretches arising due to GPO triplets respectively.…”
Section: Ir Spectral Profile Of Chmentioning
confidence: 99%
“…FTIR microspectroscopy and imaging have proven to be an excellent tool for analyzing protein structures in tissue related to microstructure (Böcker et al, 2006). The authors have previously shown that connective tissue components important for fish fillet quality were detectable with FTIR spectroscopy [19]. With Principal Component Analysis (PCA), it was possible to detect differences in the relative collagen content.…”
Section: Introductionmentioning
confidence: 99%